A Study of Required English Skills for Healthcare Personnel in Bangkok-Based International Hospitals - Pandey, Inthira (Journal of Education and Vocational Research, 2013)
The effective use of English skills is required for the Thai healthcare personnel. This study therefore aims to explore: 1) the use of the four English language skills by Thai healthcare personnel, 2) the minimum framework of effective interaction involvement for their situational contexts, and 3) the problems encountered when they communicate with foreign patients. This study revealed the following findings. Firstly, English speaking and listening skills were the two most important skills especially needed for healthcare personnel in their workplace. Secondly, grammatical errors and varieties of accents and pronunciation were seen as major communication problems. Lastly, the culture, social etiquettes, and values between healthcare personnel and foreign patients are required to build an internationally accepted reputation and meet patients’ social, cultural, and linguistic needs. This study indicates that intensive practice of the language skills is needed for healthcare personnel in preparing Thailand for the medical hub, AEC and the global market.